Learning Assessment Instrument Based on the Gamilab Game in Social Studies Subjects at Mts - Wulan Nurus Shobah; Lusty Firmantika (Universitas Pendidikan Ganesha, 2026)
Implementing learning assessments using conventional methods causes students to become bored and less motivated. This requires new innovations in learning assessment activities, one of which is using the Gamilab Game. This research aims to develop a learning assessment instrument based on the Gamilab Game in social studies subjects at MTs. This type of research uses a type of development research with the ADDIE model which consists of five development stages, namely analyze, design, development, implementation, and evaluation. The subjects in this research were 32 students in class VIII-B MTsN 7 Malang. The learning assessment instrument created was subjected to a content validation test with valid and reliable results and had a moderate level of difficulty and very satisfactory question differentiation. The results of product development were validated by learning evaluation expert validation which obtained a result of 95% in the very feasible category, material expert validation obtained a result of 95% in the very feasible category, media expert validation obtained a result of 93% in the very feasible category, and social studies subject teacher validation obtained a result of 93% in the very feasible category. So it can be concluded that the development of Gamilab Game-based learning assessment instrument product development is very suitable for use in learning activities. The implications of this research show that the use of the Gamilab Game in implementing learning assessments can increase student learning motivation, thereby reducing student boredom in implementing learning assessments in class.